Electrical and Magnetic Characterization of BSCCO and YBCO HTS Tapes for Fault Current Limiter Application - Lamas, Jerika S.; Baldan, Carlos Alberto [UNESP]; Shigue, Carlos Y.; Silhanek, A.; Moshchalkov, V. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Several high temperature superconductor (HTS) tapes have been developed since the late eighties. Due to the new techniques applied for their production, HTS tapes are becoming feasible and practical for many applications. In this work, we present the test results of five commercial HTS tapes from the BSCCO and YBCO families (short samples of 200 mm). We have measured and analyzed their intrinsic and extrinsic properties and compared their behaviors for fault current limiter (FCL) applications. Electrical measurements were performed to determine the critical current and the n value through the V-I relationship under DC and AC magnetic fields. The resistance per unit length was determined as a function of temperature. The magnetic characteristics were analyzed through susceptibility curves as a function of temperature. As transport current generates a magnetic field surrounding the HTS material, the magnetic measurements indicate the magnetic field supported by the tapes under a peak current 1.5 times higher than the critical current, I(c). By pulsed current tests the recovery time and the energy/volume during a current fault were also analyzed. These results are in agreement with the data found in the literature giving the most appropriate performance conductor for a FCL device (I(peak) = 4 kA) to be used in a 220 V-60 Hz grid.
Keywords: Critical current; electric variables measurement; HTS tapes; magnetic susceptibility; superconducting fault current limiter